Case report: Prolonged benefit of ESG401, a Trop2 antibody-drug conjugate, in endocrine-refractory hormone receptor-positive, HER-2 negative metastatic breast cancer - Zhao, Jing; Huang, Fengbo; Xu, Xia; Zhang, Yan; Xing, Xiaoyan; Huang, Jian; Qiu, Fuming (Frontiers in Oncology, 2024)
Breast cancer (BC) remains a leading cause of cancer-related mortality in women, with hormone receptor-positive (HR+) tumors accounting for a significant proportion of cases. Despite advancements in endocrine therapy (ET), resistance remains a challenge in metastatic settings. The use of cyclin-dependent kinases 4/6 (CDK4/6) inhibitors in combination with endocrine therapy has notably improved survival. In China, when patients develop resistance to CDK4/6 inhibitors (CDK4/6i) or face financial constraints that prevent their use, chemotherapy becomes the standard treatment approach. This highlights an urgent need for effective treatments following CDK4/6i therapy. ESG401 is a novel trophoblast cell-surface antigen 2 (Trop2) directed antibody-drug conjugate (ADC) with promising preclinical and early clinical efficacy and safety data. We report a case of a 61-year-old female with HR+HER2- metastatic breast cancer (MBC) who developed resistance to fulvestrant and subsequent chemotherapy but achieved a durable partial response (PR) lasting more than 22.5 months following ESG401 treatment. This case underscores the potential role of Trop2-directed ADCs, such as ESG401, in overcoming endocrine resistance and providing meaningful clinical benefit in heavily pretreated patients with HR+/HER2- MBC. Furthermore, the patient’s exceptionally long clinical benefit distinguishes her from other patients receiving ESG401 treatment. Further exploration of the use of ESG401 in HR+HER2- MBC patients, as well as a deeper understanding of the characteristics of patients that may impact sustained efficacy, in expanded clinical trials is warranted.